The application of carbonate and sediment budgets to assess the stability of marginal reef systems - Dee, Shannon; Zweifler, A.; Cuttler, M.; Nilsen, Jake; Bonesso, J.; O'Leary, M.; Browne, Nicola (2024)
Coral reefs and their associated landforms (carbonate islands and shorelines) are under increasing threat from the effects of anthropogenic climate change, including sea level rise (SLR). The ability of a reef to keep up with SLR depends on the rate of calcium carbonate accretion. Census-based carbonate budgets quantify rates of net calcium carbonate production on a reef and facilitate estimations of vertical reef accretion potential (RAP). To date, most carbonate budget studies have been undertaken in clear-water settings resulting in a limited understanding of how inshore reefs situated in more marginal environmental settings are functioning now and under future climate change. Here, we applied census-based carbonate framework across two inshore island reefs exposed to episodes of high turbidity within the Pilbara, Western Australia. Low net carbonate production (mean = 1.11 and 0.62 kg m−2 yr−1) was predominantly driven by low coral cover (<10%) and low calcification rates. Importantly, bioerosion rates were also low (<0.1 kg m−2 yr−1), maintaining positive carbonate budgetary states. Net sediment production rates were also low (mean = 0.06 kg m−2 yr−1) and were found to be mostly derived from coral, or mollusc material produced by invertivores. Calculated RAP estimates are below current and predicted rates of SLR, suggesting that these turbid reefs will soon struggle to keep up with increasing water depth and shoreline inundation.